Discovery of Novel Inhibitors From Medicinal Plants for V-Domain Ig Suppressor of T-Cell Activation - Muneer, Iqra; Ahmad, Sajjad; Naz, Anam; Abbasi, Sumra Wajid; Alblihy, Adel; Aloliqi, Abdulaziz A.; Aba Alkhayl, Faris F.; Alrumaihi, Faris; Ahmad, Sarfraz; El Bakri, Youness; Tahir Ul Qamar, Muhammad (Frontiers in Molecular Biosciences, 2021)
V-domain Ig suppressor of T cell activation (VISTA) is an immune checkpoint and is a type I transmembrane protein. VISTA is linked to immunotherapy resistance and it is a potential immune therapeutic target especially for triple-negative breast cancer. It expresses at high concentration in regulatory T cells and myeloid-derived suppressor cells, and its functional blockade found to delay tumor growth. A useful medicinal plants database for drug designing (MPD3), which is collection of phytochemicals from diverse plant families, were employed in virtual screening against VISTA to prioritize natural inhibitors against VISTA. Three compounds Paratocarpin K (PubChem ID: 14187087), 3-(1H-Indol-3-yl)-2-(trimethylazaniumyl)propanoate (PubChem ID: 3861164) and 2-[(5-Benzyl-4-ethyl-1,2,4-triazol-3-yl)sulfanylmethyl]-5-methyl-1,3,4-oxadiazole (PubChem ID: 6494266) having binding energies stronger than -6 kcal/mol were found to have two common hydrogen bond interactions with VISTA active site residues: Arg54, and Arg127. The dynamics of the compounds-VISTA complexes were further explored to infer binding stability of the systems. Results revealed that compound 14187087 and 6494266 systems are highly stable with an average RMSD of 1.31 Å. Further affirmation on the results were achieved by running MM-GBSA on the MD simulation trajectories, that re-ranked 14187087 as top-binder with net binding energy value of -33.33 kcal/mol. In conclusion, present study successfully predicted natural compounds that have the potential to block the function of VISTA and therefore can be utilized further in experimental studies to validate their real anti-VISTA activity.